Utilization of Online Ojek Services in Supporting Mobility of Visually Impaired Students: A Case Study at SLB Negeri Makassar - Rani, Arnida Hai (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Abstract:Mobility is an important part of the lives of blind students, especially in relation to the process of accessing education and social activities. This study aims to present a description of the use of online motorcycle taxis by blind students at SLB Negeri 1 Makassar to support their daily mobility. This study uses a qualitative approach, with a descriptive exploratory type. Data collection was carried out through in-depth interviews with 3 blind students. The results of the study showed that the use of maxims had a positive impact, creating the possibility of being able to travel independently without a companion. However, challenges related to application access and social interaction with drivers are still a challenge in themselves. This study highlights the importance of improving the display interface to be more accessible and inclusive training for related service providers. These findings are expected to be a reference material for improving the quality of existing transportation systems, especially for people with disabilities including the blind.Keywords:Online motorcycle taxis, maxims, mobility, blind students